General History, History in the Detail - Darragon, Eric (Groupement d'intérêt scientifique (GIS) Archives de la critique d’art, 1997)
Historians have been gripped by a fierce desire for lucidity. This is prompting them to reconsider, in a different light, the early years of the 20th century, with which we seemed to be familiar through such figures as Schwitters, Mondrian, Dali, and Matisse. Alas, whatever we did know thanks to them, we did not know well enough, but we would get to know it better through people such as otto Dix, Giorgio de Chirico, Carlo Carrà, Georg Scholz, Heinrich Hoerl, and all those who found themselves caught...